Columbia (Ship : 1787-1801) logbook - Columbia (Ship : 1787-1801)
Logbook kept by Robert Haswell and Owen Smith, of the ship Columbia. Robert Gray was shipmaster, during a voyage from Boston, Mass., to the northwest coast of America.
Microfilm edition available
Microfilm produced from original in the Manuscript Division.
Collection material in English.
Keywords: Gray, Robert, -- 1755-1806.; Haswell, Robert, -- 1768-1801.; Smith, Owen, -- active 1790.; Ports of entry -- Massachusetts -- Boston; Ship's papers -- 18th century; Voyages to the Pacific coast